The Analysis of the Application of 7Ps in Improving the Lambau Semboro Jember Billiards Service Business - Dian Hanif; Yudha Pradana; Sudarmiatin Sudarmiatin; Ita Prihatining Wilujeng (Harmoni Economics: International Journal of Economics and Accounting, 2025)
This study examines the application of the 7Ps marketing mix strategy to enhance the performance of the Lambau Semboro Jember Billiards service business. The focus is on businesses in the entertainment sector, which face challenges such as increasing competition and changing consumer preferences. The study explores how the 7Ps—product, price, place, promotion, people, process, and physical evidence—can contribute to improving customer satisfaction and loyalty. The goal is to analyze the effectiveness of each element of the 7Ps in boosting competitiveness and ensuring business sustainability. A qualitative descriptive method was used, employing triangulation techniques through in-depth interviews, participatory observation, and documentation to provide a comprehensive understanding of the marketing strategy in real-world conditions. The findings indicate that the integrated implementation of the 7Ps has supported the development of customer loyalty. Key aspects include offering a social experience through the product, competitive pricing aligned with customer value, a strategically located business, effective word-of-mouth marketing, friendly and responsive service, an efficient service process, and well-maintained physical evidence. The study concludes that consistent and comprehensive application of the 7Ps is essential for improving customer satisfaction, retention, and loyalty, thus enhancing the competitiveness of local service businesses.